An inverse problem for a hyperbolic system in a bounded domain - Cardoulis, Laure (Comptes Rendus. Mathématique)
In this Note we consider a two-by-two hyperbolic system defined on a bounded domain. Using Carleman inequalities, we obtain a Lipschitz stability result for the four spatially varying coefficients with measurements of only one component, given two sets of initial conditions.